2006
DOI: 10.1242/dev.02586
|View full text |Cite
|
Sign up to set email alerts
|

Cardioblast-intrinsic Tinman activity controls proper diversification and differentiation of myocardial cells inDrosophila

Abstract: The NK homeobox gene tinman (tin) is required for the specification of the cardiac, visceral muscle and somatic muscle progenitors in the early dorsal mesoderm of Drosophila. Like its vertebrate counterpart Nkx2.5, the expression of tin is maintained in cardiac cells during cardiac maturation and differentiation; however, owing to the complete lack of a dorsal vessel in tin mutant embryos, the function of tin in these cells has not been defined. Here we show that myocardial cells and dorsal vessels can form ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
82
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 60 publications
9
82
0
Order By: Relevance
“…Thus, sequences in the proximal 1.7-kb fragment may be required to initiate the expression in both cardioblast lineages but are only able to maintain Tin-CB expression, whereas sequences in the distal 2.6-kb fragment are required to maintain mid expression in Svp-CBs following activation. This is also consistent with the observation that mid expression is maintained in tin null embryos that have early tin expression rescued by a transgene (Zaffran et al, 2006). In these embryos, we presume that mid expression is activated by tin but maintained by tin-independent elements, like those that we propose are found in the mid2.6 fragment.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Thus, sequences in the proximal 1.7-kb fragment may be required to initiate the expression in both cardioblast lineages but are only able to maintain Tin-CB expression, whereas sequences in the distal 2.6-kb fragment are required to maintain mid expression in Svp-CBs following activation. This is also consistent with the observation that mid expression is maintained in tin null embryos that have early tin expression rescued by a transgene (Zaffran et al, 2006). In these embryos, we presume that mid expression is activated by tin but maintained by tin-independent elements, like those that we propose are found in the mid2.6 fragment.…”
Section: Discussionsupporting
confidence: 91%
“…The mid-expressing cells are selected from within clusters of cells expressing the transcription factor genes tin, pannier (pnr), which encodes a GATA factor, and Dorsocross 1, 2, and 3 (collectively referred to as Doc), which encode the Drosophila Tbx6 homologs (MiskolcziMcCallum et al, 2005;Qian et al, 2005;Zaffran et al, 2006). Lineage studies have shown that two cells in each hemisegment divide to give 6 cardioblasts (Ward and Skeath, 2000;Han and Bodmer, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas ablation of tinman in the Drosophila embryo abolishes heart formation, targeted deletion of tinman at later stages reveals additional requirements for tinman in maintaining normal adult heart function and physiology (Zaffran et al, 2006). This is reminiscent of Nkx2-5 in vertebrates, which is required for establishing heart function in the developing mouse embryo, for example, and also later for its maintenance in the adult (Pashmforoush et al, 2004).…”
Section: Cdc42-encoded Rhogtpase Is Required For Adult Cardiac Functimentioning
confidence: 99%
“…Both cell types can be subdivided into subpopulations expressing a cell subset-specific combinatorial code of transcription factors (6)(7)(8)(9)(10)(11)(12)(13). Such a subdivision suggests that different subsets of cardiac cells differentiate into functionally distinct heart components-a possibility that is supported by the finding that the Svp/Doc-positive pair of cardioblasts has the capacity to develop into the inflow tract (ostial) cells (9,14), whereas the four Tin-expressing cardioblasts adopt a cell fate of ''working myocardium'' (15).…”
mentioning
confidence: 99%